2005
DOI: 10.1111/j.1479-828x.2005.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal antecedents of moderate or severe neonatal encephalopathy in term infants – a regional review

Abstract: Background: Regional audits of term infants with neonatal encephalopathy (NE) provide an opportunity to examine issues related to causation and quality of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…Recent cohort studies involving expert examination of the fetal heart rate recordings of infants with moderate to severe encephalopathy, plus metabolic acidosis on cord blood, suggest, however, that just 15-25% had abnormal recordings in early labor that might indicate antenatal hypoxia [21,22]. The remainder either had had catastrophic events (approximately 25%) or had evidence of evolving 'nonreassuring' heart rate patterns.…”
Section: Clinical Evidence For Timing Of Injury At Termmentioning
confidence: 93%
“…Recent cohort studies involving expert examination of the fetal heart rate recordings of infants with moderate to severe encephalopathy, plus metabolic acidosis on cord blood, suggest, however, that just 15-25% had abnormal recordings in early labor that might indicate antenatal hypoxia [21,22]. The remainder either had had catastrophic events (approximately 25%) or had evidence of evolving 'nonreassuring' heart rate patterns.…”
Section: Clinical Evidence For Timing Of Injury At Termmentioning
confidence: 93%
“…10 In a regional study of moderate or severe NE in term infants, 17% were SGA. 6 SGA has consistently been associated with risk of CP. [33][34][35] Genetic, infectious, and nutritional factors can contribute to growth restriction, and defective placentation and disorders of the placenta also seem to be major factors.…”
Section: Fetal Growth Restrictionmentioning
confidence: 97%
“…Similarly, sentinel events were identified in a fairly small minority of infants with NE in controlled studies in representative populations: 7.9% 5 and 25%. 6 In a referral sample of 500 term infants with NE evaluated for therapeutic hypothermia, 48 (9%) had had a sentinel birth event. 22 Fetal bradycardia (its onset, severity, and duration unspecified) was recognized in 34% of infants.…”
Section: Acute Asphyxial Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Several epidemiologic studies have identified adverse sociodemographic factors, maternal conditions, and antenatal complications in association with NE, and these data have focused attention on the antenatal period as the origin of HIE. [9][10][11][12] However, these studies have used inclusion criteria and definitions of encephalopathy that do not limit the study cohorts to infants likely to have HIE, and the role of many antepartum and intrapartum factors in the causal pathway of neonatal HIE remains unclear.…”
mentioning
confidence: 99%